MORPHOLOGICAL FEATURES CHANGES IN THE BRAIN STRUCTURE DURING ALCOHOL INTOXICATION - Ergashev Sukhrob, (Educational Research in Universal Sciences, 2022)
Data of social and medical statistics of the last decade show a constant high level of prevalence of alcoholism and alcoholic psychosis among different groups of the population.